The city school language workbook nursery - Khan, Uzma (The City School Albakio International Lahore, 2016)
The City School's Language Workbook for nursery, while lacking color, emphasizes developing essential language skills through structured activities. It includes exercises for vocabulary building, letter recognition, phonics, and early writing. The workbook focuses on clarity and simplicity, providing engaging tasks to foster communication skills and a love for language in young learners.